Deep water echinoid-associated pontoniine shrimp “Periclimenes hertwigi Balss, 1913” species group (Crustacea: Decapoda: Caridea: Palaemonidae): species review, description of a new genus and species from Philippines - Marin, Ivan; Chan, Tin-Yam (Zootaxa, 2014)
The new pontoniine shrimp genus, Echinopericlimenes gen. nov., is suggested for four species, Periclimenes hertwigi Balss, 1913, Periclimenes dentidactylus Bruce, 1984, Periclimenes calcaratus Chace & Bruce, 1993 and Echinopericlimenes aurorae sp. nov., belonging to so-called “Periclimenes hertwigi Balss, 1913” species group sensu stricto. The new genus can be clearly separated by the unique form of hepatic tooth greatly extending beyond the pterygostomial margin of carapace, unique form of fingers of pereiopods II (chelipeds) and dactyli of ambulatory pereiopods III–V. All species referring to the new genus are similar in ecology being deep-water dwellers, usually collected deeper that 300 meters in associations with venomous sea urchins of the family Echinothuriidae (Echinodermata: Echinoidea). Remarks on ecology, description of the new species from Philippines and a key to all known species of Echinopericlimenes gen. nov. are presented.